Karakteristik Auditor Internal dan Eksternal terhadap Manajemen Laba pada Perusahaan Perbankan - Kurniawan, Fauziyyah Sukmawati; Bernawati, Yustrida (E-Jurnal Akuntansi, 2020)
Earnings management can be minimized by implementing good governance. The principles of good governance can be realized through: completeness and implementation of the committee's duties that carry out the internal control function, as well as the implementation of the audit function, and the implementation of the audit. This study shows the effect of the ratio of internal auditor certification, realization of internal auditors / audits, number of internal auditors, size of KAP, tenure of KAP, and KAP specialists on earnings management.. This study uses a quantitative approach with secondary data derived from the IDX website data. The sampling technique was carried out using a purposive sampling method. The analytical method used is multiple linear regression analysis. The results of the analysis show that the variables of the number of internal auditors, size of KAP, and tenure of KAP have a significant effect on earnings management of banking companies. Variables of certification, realization of internal auditors, and KAP specialists have no significant effect on earnings management of banking companies. Keywords: Earning Management; Internal Auditor; External Auditor.